DDX23, an Evolutionary Conserved dsRNA Sensor, Participates in Innate Antiviral Responses by Pairing With TRIF or MAVS - Ruan, Jie; Cao, Yange; Ling, Tao; Li, Peiyi; Wu, Shengpeng; Peng, Dezhi; Wang, Yao; Jia, Xin; Chen, Shangwu; Xu, Anlong; Yuan, Shaochun (Frontiers in Immunology, 2019)
DExD/H-box helicases play essential roles in RNA metabolism, and emerging data suggest that they have additional functions in antiviral immunity across species. However, little is known about this evolutionarily conserved family in antiviral responses in lower species. Here, by isolation of poly(I:C)-binding proteins in amphioxus, an extant basal chordate, we found that DExD/H-box helicases DHX9, DHX15 and DDX23 to be responsible for cytoplasmic dsRNA detection in amphioxus. Since the antiviral roles of DDX23 have not been characterized in mammals, we performed further poly(I:C) pull down assays and found human DDX23 bind to LMW poly(I:C) through its N-terminal region, suggesting that DDX23 is an evolutionarily conserved dsRNA sensor. Knockdown of human DDX23 enhanced replication of VSV and reduced activation of the NF-κB and IRF3. Moreover, when stimulated with poly(I:C) or VSV, human DDX23 translocated from nucleus to cytoplasm and formed complexes with TRIF or MAVS to initiate downstream signaling. Collectively, this comparative immunological study not only defined DDX23 as an emerging nuclear pattern recognition receptor (PRR) for innate sensing of RNA virus, but also extended the essential role of the DExD/H helicase family in viral RNA sensing from mammals to basal chordate.